Comparison of peripheral nerve block with local infiltration analgesia regarding walking ability after total knee replacement: A retrospective, propensity-score matched-pair cohort study. (19th June 2020) - Fukuda, Taeko; Imai, Shinobu; Simoda, Shunji; Nakdera, Masaya; Horiguchi, Hiromasa
Purpose: It is unclear whether perioperative analgesic techniques affect the functional outcome of total knee replacement (TKR). We investigated the effects of peripheral nerve block (PNB) and local infiltration (LI) on walking ability after TKR. Methods: The medical records of 7143 patients who underwent TKR using general anesthesia with PNB or LI techniques were reviewed. Factors affecting independence and/or improvement of walking after surgery were investigated using multivariate regression analysis. To adjust for baseline differences and minimize selection bias for the chosen analgesic technique, patients were matched by propensity scores. Results: The multivariate regression analysis showed that PNB was associated with independence and/or improvement of walking. Of the 7143 patients, 2755 (39%) received PNB analgesia and 4388 (61%) LI analgesia. After the propensity score matching, the analgesic types were not associated with walking ability. Independence reflected by the total score of daily living activities was higher in the PNB group than in the LI group. The PNB group started rehabilitation later but performed rehabilitation for longer in the initial period than the LI group. Consumption levels of fentanyl, pentazocine, and antiemetics were lower in the PNB group than in the LI group. The PNB group had fewer hypertensive episodes during surgery than the LI group. There was no significant difference in total hospitalization costs between the two groups. Conclusions: No significant difference in postoperative walking ability was found between PNB and LI groups. However, PNB offered some advantages over LI. Future detailed investigations to improve TKR surgery are needed.